El paso a la acción directa - Óscar Freán Hernández (Cahiers de Civilisation Espagnole Contemporaine)
This article will analyse the renewal of the protest action promoted by the young Spanish anarchists in exile in France during the 1960s. The purpose of this protest was not only to revive the fight against Franco’s dictatorship in Spain, but also to tackle the political stagnation of the leaders of the Spanish Libertarian Movement. This process is part of the attempt to update and adapt the anarchism to the social, economic and political changes of this period of history.